Multi-MOM : um middleware multi-paradigma, extensível e orientado a mensagens para computação móvel - Bezerra, Yuri Morais (2010)
Advances in wireless communication technologies and miniatuziation of mobile devices are leading to great opportunities in the development of applications to explore this new computing frontier. However, the development of applications for such scenarios introduces new challenges, as mobile applications run on resouce-scarce devices and communicate with each other by means of wireless networks, which are characterized by intermittent connections. In order to avoid having to deal with such issues in an ad hoc fashion for every application, middleware platforms are adopted, concealing difficulties raised by mobility from application engineers as much as possible. Due to the asynchronous and loosely coupled communication style, Message-oriented Middleware (MOM) platforms have been commonly adopted for supporting the development of networked mobile applications. However, one of the most significant limitations of current MOM for mobile platforms is that they typically support a single, predefined communication paradigm (e.g., publish/subscribe). Such a restriction limits the scope of applications supported by the middleware. In order to mitigate such a limitation, this paper presents a middleware for mobile devices capable of supporting an extensible set of message-oriented communication paradigms (e.g. tuple spaces, message queue, publish/subscribe). Supported by an integrated architecture, which has been conceived based on a Software Product Line (SPL) approach, the middleware encapsulates common features that deal with mobility issues and provides them as shared, reusable components. Evaluation results show that the overhead introduced by such a multi-paradigm approach is minimal, both in memory footprint and runtime performance. Additionally, an application scenario illustrates how mobile applications may benefit from such an approach.